2017
DOI: 10.1016/s2095-3119(16)61581-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yeast Saccharomyces cerevisiae supplementation on serum antioxidant capacity, mucosal sIgA secretions and gut microbial populations in weaned piglets

Abstract: This study was conducted to determine the effect of different forms of yeasts Saccharomyces cerevisiae supplementation on serum antioxidant capacity, mucosal secretory immunoglobulin A (sIgA) secretions and gut microbial populations in weaned piglets. A total of 96 piglets weaned at 14 d of age were randomly allotted to 4 dietary treatments: (1) basal diet without yeast (Control); (2) basal diet supplemented with 3.00 g kg-1 live yeast (LY); (3) basal diet supplemented with 2.66 g kg-1 heat-killed whole yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 58 publications
1
25
0
1
Order By: Relevance
“…Specific data referring to the effects of yeast supplementation on oxidative stress biomarkers like MDA in goats is lacking. However, our findings can be compared to the recent reports of Zhu et al (2017), who reported lower MDA levels in weaned piglets. Probably the yeast has some potential to decrease the lipid peroxidation process (Križková et al, 2001) which is reflected in a low MDA level in the current study particularly during the postpartum period.…”
Section: O N L I N E F I R S T a R T I C L Esupporting
confidence: 56%
See 1 more Smart Citation
“…Specific data referring to the effects of yeast supplementation on oxidative stress biomarkers like MDA in goats is lacking. However, our findings can be compared to the recent reports of Zhu et al (2017), who reported lower MDA levels in weaned piglets. Probably the yeast has some potential to decrease the lipid peroxidation process (Križková et al, 2001) which is reflected in a low MDA level in the current study particularly during the postpartum period.…”
Section: O N L I N E F I R S T a R T I C L Esupporting
confidence: 56%
“…Similarly, serum malondialdehyde (MDA) is also considered an excellent biomarker of lipid peroxidation (oxidative stress). A recent and limited data have reported a beneficial effect of dietary yeast on MDA level in early lactating goats during heat stress and thermoneutral period (Wang et al, 2016) and in weaned piglets as well (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nochta, I. et al reported that mannan-oligosaccharides derived from yeast fermentation products had positive effects on the immune system in weaned piglets 32 . Zhu.C et al reported that live yeast and superfine yeast powders might enhance the intestinal immunity by regulating the secretion of mucosal SIgA and reduction of pathogen colonization, thus improving intestinal health of weaned piglets 33 . Che, L. Q. et al reported live yeast supplementation in diet could alleviate the severity of diarrhea in piglets with enterotoxigenic Escherichia coli K88, which may be associated with the improved permeability, innate immunity and bacterial profile 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Piglets fed diets supplemented with live S. cerevisiae and its superfine powders had lower pH values and decreased numbers of Escherichia coli in the ileum and caecum contents compared to the control on day 21. Moreover, the ratio of Lactobacilli to Escherichia coli in the ileum and caecum contents was increased by dietary S. cerevisiae and its superfine powders (Zhu et al 2017). Finally, third possible reason for the positive effects of S. cerevisiae and L. acidophilus to improves microbial balance could be linked to their immunostimulatory effects that have been reported in different animal models (Koenen et al 2004;Li et al 2005;Ashraf and Shah 2014;Awais et al 2019).…”
Section: Microorganism Enumeration and Ph Measurementsmentioning
confidence: 94%